Knowledge sourcing by the multinational enterprise: An individual creativity-based model - Santangelo, Grazia D.; Phene, Anupama (Journal of International Business Studies, 2022)
We examine how individual heterogeneity can be managed across geographically dispersed units of the multinational enterprise (MNE) to facilitate effective knowledge sourcing. To explore individual heterogeneity, we adopt the componential theory of creativity, which links heterogeneous features of individuals to creativity performance. We propose that these features shape individuals’ responses to unit-level practices, stimulating international knowledge sourcing and sharing. We further acknowledge that MNE units are subject to the pressures for global integration and local adaptation. Individuals’ responses to unit-level knowledge transfer practices may be inconsistent with one or both of these pressures. We explore, in a nuanced fashion, conditions that can lead to such inconsistencies, and investigate how they can be resolved at the unit level to ensure effective knowledge sourcing by the MNE. Ultimately, our model challenges the assumption that individual knowledge-related efforts automatically accrue to the MNE level. We argue that effective knowledge sourcing by the MNE is the result of successful unit-level processes in managing individual heterogeneity and ensuring consistency with global integration and local adaptation pressures. Our multi-level model contributes to both the MNE- and individual-level perspective on international knowledge sourcing, and the growing microfoundations research on the role of the individual in an MNE.